1992
DOI: 10.1111/j.1600-0536.1992.tb00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch testing with pure palladium metal in patients with sensitivity to palladium chloride

Abstract: During a 15‐month period. 536 patients being investigated for suspected contact dermatitis were paid) tested with the European standard series and palladium chloride 1% pet, 13 patients (2.4%) had a positive allergic response to palladium chloride and all 13 were also allergic to nickel. 12 of these 13 patients consented to further patch testing with discs of pure palladium metal Toil, mid none reacted. We have shown previously that palladium chloride patch test material contains traces of nickel, and propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 20 publications
8
25
0
1
Order By: Relevance
“…Thirty-nine were female and 39 also reacted to nickel. Very similar results were seen in other European studies [4,5]. Our results show a higher prevalence of positive patch tests, although about only one half of our patients had a 2 or 3+ reaction.…”
Section: Commentsupporting
confidence: 80%
“…Thirty-nine were female and 39 also reacted to nickel. Very similar results were seen in other European studies [4,5]. Our results show a higher prevalence of positive patch tests, although about only one half of our patients had a 2 or 3+ reaction.…”
Section: Commentsupporting
confidence: 80%
“…Pure Pd has been previously reported to be nontoxic from local and systemic toxicity evaluations (Bessing & Kallus, ; Murdoch & Pepys, ). The reported contact hypersensitivity to palladium (Camarasa, Burrows, Menné, Wilkinson, & Shaw, ; Todd & Burrows, ) may be caused by corroded Pd ions, but it should be noted that such case reports of Pd allergy lack information about the specific dental alloys found to be problematic; other corroded ions from the dental alloy could potentially be the source of allergic reaction. Nevertheless, concerns have been expressed in the dental literature about the clinical use of dental alloys containing Pd (Wataha & Hanks, ).…”
Section: Resultsmentioning
confidence: 99%
“…Controversy persists and, to date, no prospective, randomized, appropriately controlled studies have been performed to establish the prevalence of allergic responses to Pd dental alloys. However, several reports have concluded that even in patients with documented Pd allergy, the risk of allergic reaction to Pd alloy is relatively low because of the low corrosion rate of Pd from these alloys [1,42,[49][50][51].…”
Section: Allergy To Pd or Pd Alloysmentioning
confidence: 99%
“…Palladium alloys for biomedical devices to nickel [41,50,51,[56][57][58][59]. The incidence appears to range from 93 to 100% [1].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation